Feed efficiency and enteric methane production of Nellore cattle in the feedlot and on pasture - Oliveira, L. F. [UNESP]; Ruggieri, A. C. [UNESP]; Branco, R. H.; Cota, O. L.; Canesin, R. C.; Costa, H. J. U.; Mercadante, M. E. Z. (Csiro Publishing, 2018)
The objective of the present study was to assess the relationship between residual feed intake (RFI) evaluated in a feedlot-performance test and on pasture, and to determine the effect of feedlot RFI classification on enteric methane (CH4) production in the feedlot and on pasture. Seventy-three animals (25 with a low RFI, 24 with a medium RFI and 24 with a high RFI) classified in a feedlot performance test were subjected to performance testing on Brachiaria brizantha cv. Marandu pasture. Enteric CH4 was measured in a sample of these animals (n = 47, with high and low RFI) by the sulfur hexafluoride tracer-gas technique after the feedlot-performance test and during the performance test on pasture. In the feedlot-performance test, dry-matter intake (DMI) of low-RFI animals was 9.4% and 19.7% lower (P < 0.05) than that of medium-and high-RFI animals respectively. However, there was no difference in DMI and, consequently, in RFI on pasture among animals classified as low, mediumand high RFI. Accordingly, there is evidence of re-ranking of animals for RFI performance tested in the feedlot after weaning and, subsequently, on pasture. During the period of enteric CH4 measurement in the feedlot and on pasture, the DMI, neutral detergent-fibre intake and gross-energy intake of low-RFI animals were lower than those of high-RFI animals, and low-RFI animals exhibited greater DM and neutral detergent fibre digestibility only in the feedlot. Enteric CH4 production did not differ between low-and high-RFI animals either in the feedlot (101 and 107 gCH(4)/day) or on pasture (101 and 95.9 g CH4/day). A significant difference in CH4 yield (CH4/kg DMI) was observed on pasture between animals with low and high RFI (17.6 and 13.7 gCH(4)/kg DMI respectively). The results did not support the hypothesis that an increase in feed efficiency, evaluated in growing animals in feedlot-performance tests, decreases enteric CH4 production (g/day) proportionally to the lower DMI.
Keywords: dry matter intake; performance test; residual feed intake